(untitled) (Ius Novum, 2026)
The aim of this article is to analyse the concept of aesthetic services, while also highlighting the variety of terminology used to describe the activities performed in this field. The article also attempts to define the qualifications necessary to carry out aesthetic procedures, including the qualifications that should be held by physicians performing services related to the modification or supplementation of anatomical structures. The purpose of addressing this issue is to present the scope of the problem and to indicate that regulatory gaps concerning aesthetic services contribute to the de-professionalising of medical profession, the absence of rules establishing principles governing interference with the human body, and an increased risk to individuals who undergo aesthetic procedures performed by persons from outside the medical community. The discussion is limited to Polish law, due to the significant diversity of solutions regarding aesthetic medicine services in other countries. The analysis conducted leads to the conclusion that the lack of legal regulations concerning the classification of healthcare services, their identification with healthcare services, as well as the absence of provisions defining the qualifications for their performance result in conceptual and classification chaos. This lack of clarity prevents the identification of instances in which persons performing such procedures exceed their professional competences, due to the absence of regulations specifying a catalogue of persons authorised to undertake such activities. There is an urgent need to regulate this matter, not only by standardising the certification process for medical skills in the field of aesthetic and reconstructive medicine, but also by introducing rules defining the principles of performing aesthetic procedures by persons practising medical professions other than that of physician, as well as by persons who have no formal connection to healthcare.